Общие принципы адаптации текста древнерусской летописи в хронике быховца - Морозова, Н. А. (Kalbotyra, 1991)
The article is devoted to the analysis of linguistic features or one of the most interesting Belorussian-Lithuanian chronicle by Bychovec. The main aim of the article is to explain the adaptable features of ancient Russian text in Bychovec chronicle. The analysis shows that all layers of the language have adapted: phonetical, morphological, lexical. The degree or adaptation in separate extracts of the ancient Russian text is not the same.